2023
DOI: 10.7250/bjrbe.2023-18.594
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Green Logistics in Road Transportation

Abstract: The article presents an analysis of academic literature in an attempt to identify the importance of the implementation of green logistics in road transportation. Areas of concern as well as solution and implementation opportunities are presented. A research of transportation companies was conducted in an attempt to understand the real situation regarding the implementation of green logistics measures. The research results are presented in the article. Solutions are provided in the form of a conceptual model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Some researchers identify the legal, social, ecological and technological factors for the implementation of green logistics measures and emphasise that they are equally important [4]. Also, based on the study carried out by these authors, and given that the aim of this study was to identify the risks involved in the implementation of green transport logistics measures and the reasons for their avoidance, financial, time-related, failure-related and psychological factors have been identified as the main drivers that lead to the risks involved in the implementation of green transport logistics measures.…”
Section: [18]mentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers identify the legal, social, ecological and technological factors for the implementation of green logistics measures and emphasise that they are equally important [4]. Also, based on the study carried out by these authors, and given that the aim of this study was to identify the risks involved in the implementation of green transport logistics measures and the reasons for their avoidance, financial, time-related, failure-related and psychological factors have been identified as the main drivers that lead to the risks involved in the implementation of green transport logistics measures.…”
Section: [18]mentioning
confidence: 99%
“…Also, based on the study carried out by these authors, and given that the aim of this study was to identify the risks involved in the implementation of green transport logistics measures and the reasons for their avoidance, financial, time-related, failure-related and psychological factors have been identified as the main drivers that lead to the risks involved in the implementation of green transport logistics measures. This source, which included a survey of Lithuanian transport companies and interviews with foreign transport enterprises, revealed that funding, a lack of state support and low technology transferability are the main factors preventing transport companies from implementing green logistics measures [4].…”
Section: [18]mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the misallocation between supply and demand of toll expressways still exists in the low-carbon perspective. In reality, the construction of toll expressways cannot only consider economic attributes, but also need to examine environmental attributes 38 . The phenomenon of resource misallocation in expressways leads not only to a loss of economic total factor productivity within the industry 39 , but also potentially inflicts significant harm on the climate and ecological environment 40 .…”
Section: Hypothesesmentioning
confidence: 99%
“…Cluster #5 refers to green development, focusing on topics such as green belts and roads, political ecology perspective, extended infrastructure landscape, and gateway projects. Jarasuniene and Bazaras conceptually explained the meaning of green logistics and suggested some conceptual perspectives to improve transportation sustainability [29]. Ballantyne and Pickering assessed the impact of urban trails on the environment, including soil and vegetation [30].…”
Section: Keyword Clustering Analysismentioning
confidence: 99%